Biogenic nanoparticles from bacteria: a perspective on integrated applications in sustainable agriculture - Bilesky-Jose, Natalia; Lima, Renata (Frontiers in Microbiology, 2025)
The growing demand for sustainable agricultural solutions has driven the development of technologies that contribute to modern agriculture, which aims to achieve greater productivity while maintaining environmental responsibility. Biogenic nanoparticles (BNPs) synthesized using bacteria are emerging as a promising alternative to conventional methods, offering a green approach for producing nanomaterials with agricultural applications. This Perspective highlights the mechanistic basis of bacterial nanoparticle biosynthesis and strategies for genetic and metabolic optimization to enhance yield and functionality, accentuating their potential applications as phytosanitary agents and controlled-release fertilizers. We further propose an integrative “BNP–Plant–Microbiome” framework, in which microbial consortia and multi-nanoparticle formulations could synergistically deliver nutrients, boost stress resilience, and suppress pathogens. Future progress will depend on addressing key challenges in biosafety, regulatory compliance, and large-scale bioprocessing, as well as integrating BNPs with precision agriculture and data-driven monitoring tools. Ultimately, bacterial BNPs have the potential to redefine agricultural sustainability by coupling microbial innovation with circular, resource-efficient crop management systems.